FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PEGAWAI KANTOR CAMAT KECAMATAN LIMUN KABUPATEN SAROLANGUN - . DAHMIRI (Jurnal Manajemen Terapan dan Keuangan, 2015)
This study entitled Factors Employee Work Motivation Head Office Lemonade Sarolangun. This study aimed to analyze the factors that influence the motivation of employees working at Head Office Lemonade Sarolangun. The method used was a descriptive study using a questionnaire as a tool to collect data. The population in this study were employees of Head Office Lemonade Sarolangun. Data collection procedures conducted by distributing questionnaires to a sample of all employees amounted to 34 employees. Results of this study indicate that factors Physiological Needs with an average of 126 means that it works motivated, Factor Security Needs with an average of 108.33 means that it works poorly motivated, Social Needs Factors with an average of 97.66 means that it works less motivated , Factor Needs Self-Esteem with an average of 115.66 means that it works poorly motivated, and Self-Actualization Needs factor with an average of 127.66 means that it works motivated. When viewed as a whole work motivation Sarolangun Head Office Lemonade average of 115, which means it works less motivated.